2013
DOI: 10.3201/eid1909.130013
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Genotype 4, Nanjing, China, 2001–2011

Abstract: During 2001–2011, hepatitis E virus (HEV) was found in the blood of patients in Nanjing, China. All HEV-positive patients had virus genotype 4; subgenotype 4a was predominant. The effective population of HEV in Nanjing increased in ≈1980 and continued until ≈2003 when it plateaued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…Evolutionary history and population dynamic studies show that HEV has evolved through a number of steps, in which the ancestors of HEV adapted to a succession of animal hosts, including humans (167) (168). This is in line with other studies that observed within China a decrease in the prevalence of HEV1 accompanied by an increase in the prevalence of HEV4 (169,170).…”
Section: Molecular Epidemiologysupporting
confidence: 80%
“…Evolutionary history and population dynamic studies show that HEV has evolved through a number of steps, in which the ancestors of HEV adapted to a succession of animal hosts, including humans (167) (168). This is in line with other studies that observed within China a decrease in the prevalence of HEV1 accompanied by an increase in the prevalence of HEV4 (169,170).…”
Section: Molecular Epidemiologysupporting
confidence: 80%
“…In contrast, genotypes 3 and 4 underwent an increase in population size starting in the late 19th century. However, a recent study in Nanjing, China, suggested that genotype 4 underwent a relatively recent expansion, in the late 20th century, with no change in the dominant subgenotype 4a over the past decade (168). This is in line with other studies that observed within China a decrease in the prevalence of HEV1 accompanied by an increase in the prevalence of HEV4 (169,170).…”
Section: Molecular Epidemiologysupporting
confidence: 80%
“…The ICTV study group has not defined a permanent system for classification under genotype level (subgenotype or subtypes); however, it has recommended the use of approaches based on labelling clades according to tree topology (Smith et al., ). Thus, genotype HEV‐3 has been divided into three subgenotypes 3.1 (or G3 group 1), 3.2 (or G3 group 2) and 3.3 (Oliveira‐Filho et al., ; Ijaz et al., ), and genotype HEV‐4 has been divided into seven subgenotypes 4 a–g (Dai et al., ).…”
Section: Current Nomenclature Of Hevmentioning
confidence: 99%